Peningkatan upaya pencegahan dan penanganan hipertensi melalui Posbindu PTM di Desa Teratak Buluh, Kabupaten Kampar - Zahtamal Zahtamal; Ridha Restila; Rita Endriani; Muhammad Adzan Ramadhan; Syarifah Na’imi Aqila; Nabillah Nastiti Wardhana; Muhammad Naufal Musyaffa Salim; Friska Meliana Putri; Andini Fesya Putri; Khaiziana Syaputri; Aulia Rizky Agita Nasution; Santo Gwee; Muhamad Nur Mahmudi (Unri Conference Series: Community Engagement, 2022)
Hypertension contributes to the incidence of heart disease, stroke, kidney failure, premature death, and disability. One of the community-based efforts is the Posbindu PTM. The purpose of this community service activity is to optimize education about hypertension to the community and cadres so that it is expected to: increase the knowledge of cadres about prevention and control of hypertension, provide counseling to PTM Posbindu cadres on how to educate the public about hypertension and training on the use of flipchart media to cadres Posbindu PTM, improve the skills of cadres in measuring health status and provide educational media and guidebooks to health cadres.The method used in this community service activity is in the form of a question and answer lecture discussion for community groups and cadres and training on measuring health status for PTM Posbindu cadres. In addition, cadres are also given educational media and guidebooks to optimize educational activities for the prevention and treatment of hypertension. The results of the evaluation of the activities showed that there was an increase in the knowledge of the participants before and after the counseling. The availability of hypertension education media, namely guidebooks and flipcharts from the community service team to the village, as well as tools that can support the implementation of the PTM Posbindu, namely scales, microtoise and digital blood pressure measuring devices. Then a demonstration and simulation of how to measure health status has been carried out.